Powder-basalt in the development of lettuce plants and population dynamics of insects - Groth, Mártin Zanchett; Bellé, Cristiano; Bernardi, Daniel; Borges Filho, Raul da Cunha (Revista de Ciências Agroveterinárias, 2018)
The aim of this work was to evaluate effect of the application of basalt powders from three different origins via soil (incorporation) and aerial (spraying) application in the performance of lettuce plants and in the population dynamics of phytophagous insects, respectively. Lettuce seedlings cv. Verônica at 8 days after emergence were transplanted to raised beds after the incorporation of the basalt powders. The effects on plant development were evaluated 50 days after transplantation and the parameters assessed were: plant height, growth of root system, dry mass, insertion diameter, volume of the root system and chlorophyll and carotenoid contents. Insect population dynamics was performed after the application of 100 g of basalt powder diluted in two liters of water (2 L ha) through four sprayings with intervals of 10 days between each. Sampling was performed daily and the insects collected were separated and identified. There was a significant increase in the variables plant height, growth of root system and dry mass in the treatments with the incorporation of basalt powder in the soil when compared to the control treatment. There was also a significant increase of 36% and 20% in the chlorophyll and carotenoid contents in lettuce leaves, respectively. There was no significant difference in the volume of the root system and insertion diameter between the treatments. The aerial spraying on lettuce plants with different basalt powders directly influenced the insect population dynamics with a significant decrease in the number of insects collected in all treatments.